What do you do with an idea? - Yamada, Kobi; Besom, Mae.; Forster, Sarah (Management consultant); Clark, M. H.; Riedler, Amelia; Flahiff, Julie ([Seattle, WA] : Compendium Kids, 2013)
This is the story of one brilliant idea and the child who helps to bring it into the world. As the child's confidence grows, so does the idea itself. And then, one day, something amazing happens.
Keywords: Self-actualization (Psychology) -- Juvenile fiction; Inspiration -- Juvenile fiction; Creative ability -- Juvenile fiction; Inspiration -- Fiction; Creative ability -- Fiction; Self-esteem -- Fiction; Picture books for children